Local Populations of Arabidopsis thaliana Show Clear Relationship between Photoperiodic Sensitivity of Flowering Time and Altitude - Lewandowska-Sabat, Anna M.; Fjellheim, Siri; Olsen, Jorunn E.; Rognli, Odd A. (Frontiers in Plant Science, 2017)
Adaptation of plants to local conditions that vary substantially within their geographic range is essential for seasonal timing of flowering, a major determinant of plant reproductive success. This study investigates photoperiodic responses in natural populations of Arabidopsis thaliana from high northern latitudes and their significance for local adaptation. Thirty lineages from ten local A. thaliana populations, representing different locations across an altitudinal gradient (2-850 m a.s.l.) in Norway, were grown under uniform controlled conditions, and used to screen for responses to five different photoperiods. We studied relationships between variation in photoperiodic sensitivity of flowering time, altitude and climatic factors associated with the sites of origin. We found that variations in responses to photoperiod are significantly correlated with altitude and climatic variables associated with the sites of origin of the populations. Populations originating from lower altitudes showed stronger photoperiodic sensitivity than populations from higher altitudes. Our results indicate that the altitudinal climatic gradient generates clinal variation in adaptive traits in A. thaliana.